The #MeToo movement and attitudes toward President Trump in the wake of a sexual misconduct allegation. (20th October 2022) - Klar, Samara; McCoy, Alexandra
ABSTRACT: Did sexual misconduct allegations against President Trump affect evaluations of him, particularly among supporters of the #MeToo Movement? In this research note, we present two-wave panel data from a nation-wide sample of 800 Americans conducted immediately before and after a widely publicized accusation of sexual misconduct against Trump. By comparing individuals who had heard about the new accusation against those who had not, we identify if and for whom a new accusation affects views of President Trump. Among Democrats, we find that support for #MeToo is associated with a greater belief in Trump's accusers and a reduction in approval of the president following a new allegation. Among Republicans, we find no evidence that support for the #MeToo movement affects evaluations toward the President when a new accusation arises. Overall, this study demonstrates both the stubborn persistence of presidential evaluations, as well as evidence that an accusation of sexual assault does erode his popularity – but only among his critics.